Reproductive Tract Infections: Prevalence and Associated Socio Demographic Factors among Married Women in Rural Areas of Aligarh (Indian Journal of Public Health Research & Development, 2024)
Background: Reproductive Tract Infection (RTI) is a broad term that includes Sexually Transmitted Infections(STI). This is a major public health problem worldwide, affecting the quality of life and causing serious morbidity and mortality. They have a direct impact on reproductive and child health through infertility, cancers, and pregnancy complications, and they have an indirect impact through their role in facilitating the sexual transmission of the human immunodeficiency virus.Objectives: To find the prevalence and determinants of RTI/STI among married women of reproductive age group in rural areas of Aligarh.Methods: A community-based cross-sectional study was conducted in the peri-urban and rural field practice areas of the UrbanHealth Training Center(UHTC), and Rural Health Training Centre(RHTC), J N Medical College, Aligarh, for a period of 1 year. The data were collected by using a pretested, semi-structured with both open and closed-ended questionnaire from 500 married women of reproductive age group.  Married females who had given consent and residing for more than 6 months in the field areas were included in the study. Those females having any chronic illness and not given consent were not included in the study.Statistical analysis used: Frequency, proportion and chi square test applied using 20.0 software.Results: Prevalence of RTI/STI symptoms was found to (42.8%) in rural areas.RTI symptoms were found in study subjects having lower educational status, who were not using any contraceptive method, not following good menstrual hygiene, early marriage age had husband history of RTI/STI, had a history of abortion, had a history of violence, and increased parity.Conclusions: Prevalence of symptoms found to be associated with these females having low educational status, early age of marriage, high parity, partner history of reproductive Tract Infections, history of violence etc.
Keywords: Cross sectional study, determinants, educational status, socio economic status.